Tracking chemical changes in a live cell: Biomedical applications of SR-FTIR spectromicroscopy. Issue 2 (2003) - Holman Holman, Hoi-Ying N. Hoi-Ying N.; Martin Martin, Michael C. Michael C.; McKinney McKinney, Wayne R. Wayne R.
Abstract : Synchrotron radiation-based Fourier transform infrared (SR-FTIR) spectromicroscopy is a newly emerging bioanalytical and imaging tool. This unique technique provides mid‒infrared (IR) spectra, hence chemical information, with high signal-to-noise at spatial resolutions as fine as 3 to 10 microns. Thus it enables researchers to locate, identify, and track specific chemical events within an individual living mammalian cell. Mid-IR photons are too low in energy (0.05−0.5 eV) to either break bonds or to cause ionization. In this review, we show that the synchrotron IR beam has no detectable effects on the short- and long-term viability, reproductive integrity, cell-cycle progression, and mitochondrial metabolism in living human cells, and produces only minimal sample heating (<0.5°C). We will then present several examples demonstrating the application potentials of SR-FTIR spectromicroscopy in biomedical research. These will include monitoring living cells progressing through the cell cycle, including death, and cells reacting to dilute concentrations of toxins.